1987
DOI: 10.1097/00000658-198701000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Free Perforation and Perforated Abscess in 30 Patients with Crohnʼs Disease

Abstract: Spontaneous free perforation is an uncommon event in the natural history of Crohn's disease. It occurred in 21 of 1415 patients (1.5%) admitted with Crohn's disease to The Mount Sinai Hospital between 1960 and 1983. The mean duration from onset of Crohn's disease to occurrence of perforation was 3.3 years. Ten patients had small bowel perforation, ten patients had large bowel perforation, and one patient had simultaneous perforation of both ileum and cecum. The incidence of perforation in disease segments of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 32 publications
1
58
0
2
Order By: Relevance
“…IBDs are rare conditions associated with development of GI perforation and fistula (particularly for Crohn disease). [56][57][58] In the current study, though a history of IBD or treatment thereof was reported in Ͻ 1% of the study population, those with a history of treatment for IBD had a 13-fold higher odds of a GI AE compared with those without such history.…”
Section: Wwwjcoorgmentioning
confidence: 69%
“…IBDs are rare conditions associated with development of GI perforation and fistula (particularly for Crohn disease). [56][57][58] In the current study, though a history of IBD or treatment thereof was reported in Ͻ 1% of the study population, those with a history of treatment for IBD had a 13-fold higher odds of a GI AE compared with those without such history.…”
Section: Wwwjcoorgmentioning
confidence: 69%
“…Greenstein et al 10 suggested that increased intraluminal pressure proximal to the stricture and ischemia due to in- In the current case, free perforation was likely caused by rapid and markedly increased intraluminal pressure proximal to the severe strictures, secondary to a large amount of food intake over a short time due to the therapeutic effectiveness of infliximab and relief of inflammation of the intestinal wall due to the effects of the drug. Previous studies have reported that cytokines, such as TNF-α, can influence human behavior during inflammatory conditions.…”
Section: Introductionmentioning
confidence: 64%
“…Ten patients had small bowel perforation, ten patients had large bowel perforation, and one patient had simultaneous perforation of both ileum and cecum. The incidence of perforation in disease segments of small bowel was 1.0% (jejunum 6.0%, ileum 0.7%), and in the colon, 1.3 % [3]. In a study by Freeman from Canada, 15 new cases of spontaneous free perforation of the small intestine (nine females and six males) were discovered in a series of 1000 consecutively evaluated patients with Crohn's disease seen during a period spanning 20 years, for an estimated frequency of 1.5%.…”
Section: Discussionmentioning
confidence: 96%
“…The accompanying fibrous reaction and adhesion to adjacent viscera appears to limit the complication of free perforation in some cases. The mean disease duration is 3.3 years before free perforation [3,7]. In a study by Katz et al, the patient with isolated jejunal perforation has disease duration of 10 years before perforation [6].…”
Section: Discussionmentioning
confidence: 99%